Reaction rate measurements between sympathetically cooled ions and velocity selected polar molecules: search for the deuterium isotope effects. (July 2015) - Takada, Yusuke; Okada, Kunihiro
Synopsis: The rates of cold ion-polar molecule reactions are measured at a temperature lower than 10 K in order to search for the deuterium isotope effects.